Corporate Tax Avoidance and Corporate Social Responsibility Disclosure Readability: Evidence from China. Issue 2 (8th May 2022) - Xu, Shuolei; Wang, Fangjun; Cullinan, Charles P.; Dong, Nanyan
Abstract: Paying taxes to support the societies in which they operate is both a legal and ethical responsibility of business. Nevertheless, some companies work to avoid taxes, which could cause society to question the legitimacy of the organisation. Many companies provide reports on their corporate social responsibility (CSR) activities; more transparent CSR reports may help to restore the legitimacy loss associated with tax avoidance. We investigate the relationship between tax avoidance and CSR report readability among Chinese companies. We find a positive relationship between corporate tax avoidance and the readability of CSR reports. This relation is weaker among state‐owned enterprises, which may have stronger pre‐existing legitimacy owing to their relationship with the state. The relationship is also weaker among companies in less developed regions of China, which have less developed institutions to monitor organisational legitimacy. Overall, our results are consistent with the notion that CSR reporting represents an attempt to overcome legitimacy concerns arising from tax avoidance. Our findings indicate that tax avoidance and CSR reporting are alternative means of establishing legitimacy, rather than complementary reflections of an organisational culture that values (or devalues) CSR.